Transformasi Kesehatan Masyarakat Melalui Peningkatan Fasilitas Sanitasi di Kecamatan Tomo: Analisis dan Proyeksi 2024 - Hakim, Abdul; Fahreza, Mohammad; Nurpadi, Dady (Coopetition : Jurnal Ilmiah Manajemen, 2024)
Sanitation facilities, especially defecation facilities, play a vital role in reducing the spread of infectious diseases associated with poor sanitation. Tomo District has made various efforts to improve access to sanitation, including the construction of public toilet facilities and health education campaigns. However, there are still challenges in achieving universal sanitation coverage. This study aims to identify the distribution of defecation facility use in Tomo District from 2019 to 2021, measure the level of public health in Tomo District during that period. analyze the relationship between the type of defecation facility and the level of public health. And projecting changes in the use of drinking water sources and disease prevalence. This study uses a quantitative approach with descriptive and inferential analysis to evaluate the relationship between the independent variables (defecation facilities) and the dependent variable (health level). With the projection of data on the use of drinking water sources and the prevalence of infectious diseases until 2024, we can see the expected trend if the assumption of an increase or decrease of 10% each year is met. These results provide an important picture for planning and decision making in efforts to improve public health in Tomo District. The results showed a significant relationship between the use of private latrines and a decrease in the prevalence of infectious diseases such as diarrhea and digestive tract infections